The prescription pattern and awareness about antibiotic prophylaxis and resistance among a group of Egyptian pediatric and general dentists: a cross sectional study - Mariam Mohsen Aly; Marwa Aly Elchaghaby (BMC, 2021)
Abstract Background The use of antibiotics in dentistry as prophylaxis and treatment is frequent. Their misuse has led to a major public health problem globally known as antibiotic resistance. This study aimed to assess the pattern of antibiotic prescription and its prophylactic use for systemic conditions. Besides, this study evaluated the awareness and adherence to antibiotic prescription guidelines and antibiotic prophylaxis guidelines along with awareness of antibiotic resistance across pediatric and general dentists. Methods An overall of 378 pediatric and general dentists meeting the required eligibility criteria, fulfilled a pre-designed validated questionnaire. Data were collected, tabulated, and statistically analyzed. Results A significant statistical difference was found among the pediatric and general dentists regarding antibiotics prescription for most of the oral conditions where Amoxicillin with clavulanic acid was the most frequently prescribed antibiotic among the two groups (53% pediatric dentist and 52% general dentist). The majority of pediatric and general dentists, on the other hand, were aware of antibiotic resistance and prescribing recommendations. Conclusions The present study showed a tendency to overprescribe and overuse antibiotics in certain dental conditions among the participants. The vast majority of dentists, especially general dentists do not have adherence to professional guidelines for antibiotics prescription in children despite their awareness of antibiotic resistance and prescription guidelines.